Penerapan Metode Ummi Dalam Meningkatkan Bacaan Al-Qur’an Anak Usia 5-6 Tahun - Shafa, Gitanti Yayang; Istiqlaliyah, Hulailah (An-Nuha, 2024)
The Ummi method has become a learning model for reading the Qur'an that has spread in the community. The purpose of this study is to determine the application of the UMMI method in improving the reading of the Qur'an in Al-Anwariyah Kindergarten, North Jakarta. This study used a type of descriptive qualitative research. The data collection method is carried out by observation, interviews, and documentation. The data analysis techniques are data reduction, data presentation, and conclusion drawing with primary data sources and secondary data. The application of the UMMI method has 3 steps in learning, namely completing volume 1 of the UMMI method, in the implementation of students reading volume 1 using individual techniques, individual classical, classical reading listen, and classical reading simak pure, in evaluation the teacher carries out an evaluation at the end of learning the UMMI method by telling children to reread volume 1 books.